Pengaruh Media Bermain Pasir Kinetik Terhadap Aspek Motorik Halus Anak Usia 5-6 Tahun Di TK Pelangi Kasih Siborongborong Kabupaten Tapanuli Utara - Santi Nababan; Winarti Agustina; Hisardo Sitorus (Coram Mundo: Jurnal Teologi dan Pendidikan Agama Kristen, 2023)
The aim of this research was to determine the effect of kinetic sand playing media on the fine motoric aspects of children aged 5-6 years at Pelangi Kasih Siborongborong Kindergarten, North Tapanuli Regency. The method used in this research is a descriptive quantitative research method. The population was all children aged 5-6 years at Pelangi Kasih Siborongborong Kindergarten, North Tapanuli Regency, totaling 54 people and a sample of 20 people was determined using a non-probability sampling technique, namely purposive sampling. Data was collected using a 25-item positive closed questionnaire. The results of data analysis show that there is a positive influence between kinetic sand playing media on the fine motoric aspects of children aged 5-6 years at Pelangi Kasih Siborongborong Kindergarten, North Tapanuli Regency: 1) Analysis requirements test: a) positive relationship test obtained rxy = 0.599 > rtable(=0.05,n=20) = 0.444, thus it is known that there is a positive influence between variable dk=n-2=18)= 2.101, thus there is a significant influence between variable Y ̂="23","22"+0.78X. Thus Ha is accepted and H0 is rejected.